Penerpan Regional Environmental Simulator (RES) Untuk Simulasi Dinamika Muara Perairan Semarang - Fitri Riandini (JURNAL SUMBER DAYA AIR, 2010)
Estuaries are multi-functional environments. Their eco-system is of great importance for wildlife; wetlands are often found, serving as a nursery for fish and birds. At the same time, human activity in estuaries is high, often stressing the ecological function of these environments. Because estuaries (where a river enters the sea) are conveniently situated for trade, estuarine environments have nearly always been densely populated areas. Availability of fresh water for cooling water or washing equipment makes high possibility of wasting waters. One of parameter which is harmful for water environment is sediment in huge contains. Some problems will appear, such as high turbidity which is blocking sun shine, sedimentation, or closing river mouth.Semarang is capital city of Central Java Province, located at northern part of this province. As a coastal city a lot of rivers ended at Semarang coastal water and transport the sediment. One of effect of sediment transport is sedimentation and further morphological change.In this study a 3-dimensional hydrodynamics and sediment transport model (ECOMSED) as a part of system called Regional Environmental Simulator (RES) have applied to simulate estuary dynamic of Semarang coastal waters, especially around Kali Garang. The model can be used to predict environment condition and disaster prevention. Simulation results shown that circulation of Semarang coastal water dominated by river discharge rather than sea tide, and transport the sediment from river to the coast.